Characteristics of the Kama Neolithic Culture Pottery (based on a comprehensive analysis of wares from Khomutovskoe Boloto I-II campsites) - Evgeniia L. Lychagina; Nadezhda S. Smertina; Denis A. Demakov (Археология евразийских степей, 2025)
The article presents the results of typological, technical-technological, and petrographic analyses of pottery from the Khomutovskoe Boloto I and II sites, located in the Northern Kama region. The sites are characterized by vessels in sandy and brown colors, with wall thicknesses of 8–10 mm. Vessel surfaces were smoothed with a soft object, and slanted or rounded rims predominate, while an interior rim coil (clay ridge) is rarely encountered. The primary decoration techniques are impression (stamping), rolling (dragging), and punctate stamping ("stepping"). Patterns were applied using a comb stamp, sometimes combined with pit ornamentation. Vessels were made from non-sandy silty clays and clays, most often used in a dry, crushed state. The main temper in the paste was grog of varying sizes (0.5–5 mm). The described characteristics are typical for the pottery of the early stage of the Kama Neolithic culture. The pottery assemblages from the Khomutovskoe Boloto I and II sites can be considered as standard examples for characterizing the Kama pottery tradition.